INCA ARCHITECTURE THROUGH YOUR TEXTILES PERU- FAUA / UNI - Gonzales Arnao, Walter (2014)
We propose a look at incas textiles and planimetric support of its territory an Inducing reflection on the possible applications of textiles in architecture incas, and bring out the eyes of designers, architects and engineers with the hypothesis of the value and application of incas textiles in representing three-dimensional surveying of the material world as conceived. Test ideas about the uses of the art of weaving and its influence on Inca architecture. Use this ancient knowledge an instrument of inspiration for future architects.